THE EFFECT OF LACK OF SUPERVISION ON THE DANGER OF BULLYING AT THE HOUSE FOR ORPHANTS AND DHUAFA AULIA PONDOK PETIR BOJONGSARI DEPOK - Apriansyah, Muger; Syahnego, Syahnego; Irawati, Laila (Yayasan Education and Social Center, 2024)
An orphanage is a social institution that provides protection, care and education for children who are neglected, orphaned or do not have families who are able to care for them. The background to the establishment of an orphanage is closely related to various social, economic and cultural factors that exist in society. Overall, the background to the establishment of orphanages involves a combination of complex social, economic, cultural and policy factors. Although the main goal is to provide protection and education for children in need, challenges and changes in society continue to influence the role and function of orphanages in responding to the needs of neglected children. However​ at the orphanage care sometimes Where does the problem of bullying occur ? matter the is a serious situation and can impact the emotional and mental well-being of the children living there. Method used​ in activity devotion public This is with give training and socialization To use build pattern think and be enthusiastic children House For understand and can